2021
DOI: 10.1007/s43032-021-00660-w
|View full text |Cite
|
Sign up to set email alerts
|

The Downregulation of Placental Lumican Promotes the Progression of Preeclampsia

Abstract: Multiple pieces of evidence illustrate that impaired trophoblast function results in preeclampsia (PE), and migration/invasion of human trophoblast cells is stringently regulated by extracellular matrix (ECM) components. Many studies have indicated abnormal expressions of placental ECM components are associated with preeclampsia. However, the change and influence of lumican, a vital member of extracellular matrix (ECM) molecules, on trophoblast cells during preeclampsia remain unclear. This study examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…A separate study of amniotic fluid proteins using mass spectrometry and validation by ELISA identified lumican (LUM), apolipoprotein (APOA4), and kininogen-1 (KNG1) as biomarkers of preterm birth 38 . Lumican is a major proteoglycan expressed in the cornea and skin, as well as the placenta, where it is hypothesized to play a role in preeclampsia 39 . In our study, LUM was the 9th most abundant protein in human amniotic fluid and the 22nd most abundant in rhesus amniotic fluid, and was downregulated in both species with increasing gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study of amniotic fluid proteins using mass spectrometry and validation by ELISA identified lumican (LUM), apolipoprotein (APOA4), and kininogen-1 (KNG1) as biomarkers of preterm birth 38 . Lumican is a major proteoglycan expressed in the cornea and skin, as well as the placenta, where it is hypothesized to play a role in preeclampsia 39 . In our study, LUM was the 9th most abundant protein in human amniotic fluid and the 22nd most abundant in rhesus amniotic fluid, and was downregulated in both species with increasing gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Recent studies have suggested that impaired trophoblast function can lead to PE, and human trophoblast cell migration/invasion is tightly regulated by the ECM. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…[18] Recent studies have suggested that impaired trophoblast function can lead to PE, and human trophoblast cell migration/invasion is tightly regulated by the ECM. [19] Despite increasing efforts to mine databases to identify molecular markers that can help diagnose and treat PE, ARGs in PE and immune infiltrates had not yet been investigated. Substantial evidence indicates that vascular disorder and deficient trophoblast invasion are involved in PE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In trophoblasts, ECM thickness affects the production of mRNA and proteins related to fusion. Abnormal expression of placental ECM components is Frontiers in Genetics frontiersin.org associated with abnormal migration/invasion of human trophoblast cells (Romanowicz and Galewska 2011;Ma et al, 2020;Liu et al, 2021;Parameshwar et al, 2021). Consequently, PE may develop due to ECM changes.…”
Section: Discussionmentioning
confidence: 99%